Proceedings of IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1996.506839
|View full text |Cite
|
Sign up to set email alerts
|

Arm-manipulator coordination for load sharing using compliant control

Abstract: Arm-manipulator coordination is a new coordination problem in robotics. Human arm-manipulator coordination is superior to both arm-arm coordination and manipulator-manipulator coordination. Likewise, it is expected to have powerful impacts on many applications in the manufacturing, service, and construction industries. This paper introduces this problem and investigates the coordination using a compliant control method. There are several problems in this scheme. First, the stability problem is studied using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Those studies can be classified into two types according to whether the human impedance property is constant during operation [9], [11], [13], or variable [10], [12], [14]. No detailed discussion has addressed how a machine adapts its dynamics for human impedance properties that would widely change depending on human posture and muscle activations during operations.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies can be classified into two types according to whether the human impedance property is constant during operation [9], [11], [13], or variable [10], [12], [14]. No detailed discussion has addressed how a machine adapts its dynamics for human impedance properties that would widely change depending on human posture and muscle activations during operations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the human-robotic cooperation system, Kosuge et al [8], [9] estimated human impedance from frequency responses using the least squares method. Al-Jarrah et al [10], [11] expressed the dynamic property of the human operator with stiffness and reported that the system stability is much influenced by the stiffness. Ikeura [13] investigated the impedance property of a human operator who manipulated a slave robot to follow the motion of the master robot that was controlled by another operator, and reported that the operability of masterslave systems can be improved by applying the estimated human impedance to the impedance control of the slave robot.…”
Section: A Human-robotic Systemsmentioning
confidence: 99%
“…The assisting signal is defined using as (10) where is the assist ratio. By changing , the amount of robotic assistance can be adjusted for a trainee.…”
Section: B Structure Of Proposed Training Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been proposed for designing and controlling a human-machine system constructed with an impedance-controlled robot [17]- [26] since the overall system can be described by the impedance property. Those studies can be classified into two types according to whether the human impedance property is constant during operation [18], [19], or variable [20], [21], [22], [23]. Some research studies addressed the method for providing the realistic feel to improve performances in the manual task [20], [25], [26], but no detailed discussion has addressed how a machine should adapt its dynamics for HMIP that would change widely depending on the NMS condition during manual operations.…”
mentioning
confidence: 99%